2022
DOI: 10.21037/tlcr-21-1038
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram to predict the recurrence-free survival and analyze the utility of chemotherapy in stage IB non-small cell lung cancer

Abstract: Background: Large part of patients of stage IB non-small cell lung cancer (IB NSCLC) may suffer recurrence after surgery. This study is to determine risk factors and establish a nomogram for postoperative recurrence and to provide a reference for adjuvant chemotherapy selection in patients with stage IB NSCLC.Methods: A total of 394 patients with postoperative stage IB NSCLC who visited Fujian Medical University Union Hospital between January 2010 and June 2016 were selected. Patients were divided into trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Some scholars have identified risk factors influencing postoperative recurrence and have constructed predictive models for recurrence, aiming to inform the selection of ACT for stage IB NSCLC patients (91)(92)(93)(94)(95)(96). However, relatively limited research has been conducted on predictive models for postoperative recurrence in patients with stage IB NSCLC featuring VPI.…”
Section: Stage Ib and Adjuvant Chemotherapymentioning
confidence: 99%
“…Some scholars have identified risk factors influencing postoperative recurrence and have constructed predictive models for recurrence, aiming to inform the selection of ACT for stage IB NSCLC patients (91)(92)(93)(94)(95)(96). However, relatively limited research has been conducted on predictive models for postoperative recurrence in patients with stage IB NSCLC featuring VPI.…”
Section: Stage Ib and Adjuvant Chemotherapymentioning
confidence: 99%
“…However, the international tumor-node-metastasis (TNM) staging system only relies on anatomical and pathological features for disease assessment, without considering many other important relevant factors, such as age, sex, and other demographic characteristics [86,87]. Numerous studies have shown that the clinical stage alone is not sufficient to predict the prognosis of patients with cancer [87][88][89][90]; therefore, further analysis of demographic characteristics is necessary [36].…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Surgery is the primary treatment for early-stage lung cancer, especially stage I non-small cell lung cancer (NSCLC). However, previous studies have reported a recurrence rate of approximately 18–29% within 5 years after surgery for stage I NSCLC ( 4 , 5 ). Therefore, it is necessary to identify risk factors for poor prognosis after surgery.…”
Section: Introductionmentioning
confidence: 96%